QARAQALPAQSTAN RESPUBLIKASÍ NEFT-GAZ INVESTICIYALÍQ BLOKLARÍNA SÍPATLAMA - Uzakbaev, Koblan Kewnimjay ulı; Tastayev, Dármenbay Muratbayevich (SCIENCE and SOCIETY, 2026)
The article describes the oil and gas resources in the territory of the Republic of Karakalpakstan, the investment blocks where they are widely distributed, and the prospects for their utilisation.